Expression of Extracellular Superoxide Dismutase Protein in Diabetes - Chul Han Kim (Archives of Plastic Surgery, 2013)
Background Diabetes is characterized by chronic hyperglycemia, which can increase reactive oxygen species (ROS) production by the mitochondrial electron transport chain. The formation of ROS induces oxidative stress and activates oxidative damage-inducing genes in cells. No research has been published on oxidative damage-related extracellular superoxide dismutase (EC-SOD) protein levels in human diabetic skin. We investigated the expression of EC-SOD in diabetic skin compared with normal skin tissue in vivo. Methods The expression of EC-SOD protein was evaluated by western blotting in 6 diabetic skin tissue samples and 6 normal skin samples. Immunohistochemical staining was also carried out to confirm the EC-SOD expression level in the 6 diabetic skin tissue samples. Results The western blotting showed significantly lower EC-SOD protein expression in the diabetic skin tissue than in the normal tissue. Immunohistochemical examination of EC-SOD protein expression supported the western blotting analysis. Conclusions Diabetic skin tissues express a relatively small amount of EC-SOD protein and may not be protected against oxidative stress. We believe that EC-SOD is related to the altered metabolic state in diabetic skin, which elevates ROS production.